Por dentro do debate Piaget-Wallon: o desenrolar da controvérsia sobre a origem e desenvolvimento do pensamento simbólico - Dener Luiz da Silva (2007)
This dissertation investigates the debate between Henri Wallon (1879-1962) and Jean Piaget (1896-1980) two authors whose work is very relevant for the history of psychology of education. The purpose of the study is to identify their controversies and to situate them in their historical and scientific contexts in the period between 1920 e 1960, a period along which both authors disputed the hegemony within the field of knowledge of genetic psychology among French speakers. Special attention is given to the controversy concerning the origin and formation of the symbolic function, taking into consideration its heuristic value for the understanding of similarities and differences between their theoretical positions regarding child and adult development. Theoretical and historical research methods were used to select and analyse the sources, taking an internalist standpoint combined with constructicionist and critical historical methods. The results show that the debate Piaget Wallon was marked by an untimely dynamics between the critiques and the stage of theoretical development of each author. When explaining the passage from sensory-motor or situational intelligence to representational thought, the centrality of this theme was replaced by peripheral considerations such as continuity or discontinuity, the value of social or maturational aspects, among others. Concerning the genesis of representation, Wallon emphasizes the path going from the body, the tonic function, of emotions, passing through pretence and imitation. Piaget aims at understanding this process as a complexification of sensory-motor schemata and the dynamics between assimilation and accomodation, identified through the analysis of imitation and play activities. Both authors agree that the birth of representation marks the establishment of a symbolic function, defined as a capacity to evoke absent objects through mental representation, relating the real object, its sign and its meaning. They agree also that, for the establishment of the symbolic function, the subjects initial experiences that culminated in the sensory-motor schemes or situational intelligence must be reactualized, through a double assimilation and accomodation, or the sublimation of spatial intuition at the representational level. For both authors, there are structural differences between practical and representational intelligence, notwithstanding their integration and functional preparation. Several factors explain the disagreements between Piaget and Wallon along almost four decades: their purposes, theoretical overviews, differential interests, linguistic problems, etc. The programs of research assumed by each author were different. Piagets research program aimed at the understanding of the processes underlying the progressive construction of knowledge by the epistemic subject, while Wallon aimed at focusing the psychological subject in his/her emotional and cognitive whole. Therefore, their approaches to representation remained diverse. For Piaget, representation is part of an act of knowledge directed towards objects of knowledge and being instruments for the cognitive process. For Wallon representation is understood as an element in the interaction with the other, an element that is charged with emotion, aiming at mobilizing the subject to approach the other with the purpose of construing a differentiated and autonomous self: the person. The investigation of this debate concerning the controversy on the formation of symbolic thought was a way for us to better understand the singular trajectories of both authors, as a testimony of an important chapter of the history of psychology, with consequences for the evolution of other fields of knowledge such as epistemology and education.